Deseamos Sobrevivir (We Want to Survive): Survival, Ecological Selves, and Regenerative Spiritual Care Praxis from South America - Hoskins, Christopher M. (Journal of pastoral theology, 2025)
Regenerative agriculture, reforestation, and cultural production prove integral to resisting economic, social, and ecological degradation in care and survival praxis among two Ecuadorian communities. One community facilitates care praxis among afrodescendiente youth facing state and criminal violence through folkloric movement, storytelling, and mangrove reforestation. In another part of the hemisphere, a group of Ecuadorian survival migrants join efforts at communal regenerative farming, strengthening local food systems while also enacting healing stories of homeland prior to drought and exploitation. Both communities resist racism, violence, and destruction by constructing a sense of self in relation to land. Carroll Watkins Ali’s pastoral theme of survival in the face of ‘genocidal poverty’ paired with ecological storytelling offer analysis and reflection from contexts and populations where the intensity of climate change greatly alters daily-life. Localized communal care and ecological selfhood stand as urgent praxis in pursuing the survival of the ecological community across the globe.